HIGH-VOLTAGE MOTORS ON-SITE TESTING - Milić, Momčilo; Jovanović, Đorđe; Ilić, Denis; Stanojević, Nikola; Kališkić, Radmila (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
High-voltage motors are one of the most important components in terms of their role and importance for the operation of power plants and industrial facilities. However, they are often not given much attention in terms of preventive maintenance. Maintenance in power plants in Serbia still takes place according to the outdated model of maintenance at time fixed intervals – time based maintenance. This is the reason why emphasis has to be placed on electrical measurements of high-voltage motors in order to have a better insight into their condition, prevent unwanted failures and improve their service. This paper will provide an overview of currently available prophylactic tests of high-voltage motors. Also the most common testing methods will be described, whose measurement results provide information of current condition in order to take possible further repairs or corrective actions. Throughout the whole work itself, it will be presented examples and experiences from practice in power plants in Serbia.Keywords: High-voltage motors - Electrical measurements.